Conversation analysis of doctor-patient interactions at the Department of Family and Community Medicine, Philippine General Hospital - Adeva, Alice B. (2003)
The study aimed to determine the interaction patterns prevalent in doctor-patient communication at the Department of Family and Community Medicine, PGH. Specifically, the research also aimed to answer the present in the communication of the doctors to their patients? And (2) What are the compliance-gaining strategies used by the doctors in medical consultations? A total of 28 doctor-patient interactions were audio and video taped. Transcripts of conversations were subjected to a three-part analysis: Interaction Profile, Relational Communication, and Compliance-Gaining Strategies. Research findings reveled that a doctor-centered interaction emerged as a pattern. Relational Message themes included dominance, receptivity, informality, composure, similarity. Most of the compliance-gaining strategies used were direct and simple instructions.
Includes bibliographical references (page 46).